Virtual reality as a learning tool: Evaluating the use and effectiveness of simulation laboratories in educational settings - Dodevska, Mila; Zdravevski, Eftim; Chorbev, Ivan; Branco, Frederico; Kostoska, Magdalena; Coelho, Paulo Jorge; Pires, Ivan Miguel; Lameski, Petre (Elsevier BV, 2025)
Virtual Reality Laboratories (VRLs) are essential progress towards educational solutions that would allow students to learn the sometimes complex experimental processes without spending physical resources. The resources used in some experiments often require significant procurement effort, significantly impacting the environment where an experiment would be conducted. The main focus of this research is to review the possibility of using VR solutions as educational tools and innovative approaches to scientific knowledge production. This paper systematically reviews relevant publications in this area while covering several existing virtual lab solutions. The analysis shows that VRL tools can be effectively used for educational purposes, allow access to lab resources for people with disabilities, and could be used to reach the desired learning outcomes. A gap exists between natural laboratories and VRLs, especially in the collaborative aspect of the laboratory exercises. However, there is significant ongoing research on this topic and a high potential for development.
Keywords: Virtual realityLaboratoriesSimulationsEducationVR in educationVirtual reality labs